KETAHANAN PANGAN DUNIA SEBAGAI DAMPAK PERANG UKRAINA RUSIA BERDASARKAN HUKUM INTERNASIONAL - Nababan, Desvo Richat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
In recent years, the war between Russia and Ukraine has had an impact on countries inthe world that are dependent on the conflicting countries in terms of food security which hascaused a food crisis which has caused world hunger rates to increase and created a situationof economic and political instability in the world. The right to food is a basic human rightrecognized in international, regional and national instruments. Therefore, the researchobjectives of this thesis are: first, to determine the impact of world food security as a result ofthe Ukraine-Russia war based on international law. Second, to find out the role of InternationalLaw in overcoming food security due to the impact of the Ukraine-Russia war.The type of research used by the author is normative legal research or what is known as"legal research". which means that legal research is conceptualized as what is written in thestatutory regulations (law in book) or law.From the research results, there are two main things that can be concluded. First, theUkraine-Russia War has implications for world food security, especially if the fighting involvesareas that are fertile and important for global food production, resulting in the destruction ofagricultural infrastructure, disrupting food production, and causing losses in global supplychains. This can lead to food shortages and increased food prices throughout the world. Inaddition, the war between Ukraine and Russia has an impact on food security that is not limitedto the conflict area, but can spread globally due to economic dependence and internationaltrade. Second, International Law plays an important role in overcoming the impact of theRussia-Ukraine war on food security. In this case, humanitarian law is present in upholdinghumanitarian principles in war situations, especially in maintaining access to world food forcountries that are food dependent on Ukraine and Russia.Keywords: Food Security, Ukraine, Russia, International Law.